The Nanomembrane Toilet: Membranes for water recovery in decentralised sanitation systems - Kamranvand, Farhad (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event 2018.In this research, the Nanomembrane Toilet is introduced as a single household sanitation system independent of grid produced power. To address paucity of information on super-concentrated wastewater characterisation, chemical oxygen demand (COD), ammoniacal nitrogen, and E.Coli bacteria are analysed in the wastewater storage tank. A small-scale combustor is developed (Onabanjo et al., 2016) to operate on the faecal sludge phase, producing low-grade heat that is used to provide the vapour pressure gradient for thermally-driven membrane separation of water from faecally contaminated urine (FCU). Subsequently, a membrane technology is developed that can provide a single-stage treatment process, separating clean water from FCU. In this study, the impact of temperature on water recovery from FCU (urine:faece 56:1) by membranes (PTFE, nominal pore size 0.1 µm) is investigated. Out of 40, 50, and 60 ⁰C operational temperature values, operation at 60 c is shown to enable the process for the removal of organics, inorganics, and pathogens, sufficient to meet the ISO/PC 305 standard for sustainable non-sewered sanitation systems (American National Standards Institute, 2016). Furthermore, influence of faecal concentration in the FCU (at optimised temperature of 60 ⁰C) on the produced water quality is studied. The results show that high faecal concentration leads to high ammonium formation in the feed, hence faster ammonia breakthrough is observed. Lastly, the membrane pore size was optimised for the treatment of FCU at constant faecal concentration and temperature. It is concluded that only 0.1 µm membrane pore size is capable of removing ammonia, COD, and E.Coli to the proposed ISO standard at both 40 and 60 ⁰C. Importantly, this study has demonstrated that through integration of this modularised componentry into the Nanomembrane Toilet, single household sanitation can be delivered, independent of external power sources and infrastructure.
Keywords: innovative technology'; 'global decentralised sanitation'; 'membrane distillation'; 'CranfieldDN2018'; 'Biotechnology'